2017
DOI: 10.1155/2017/6140896
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic Soluble Receptor for Advanced Glycation End Products as a New Oxidative Stress Biomarker in Patients with Prosthetic-Joint-Associated Infections?

Abstract: Prosthetic joint infection (PJI) is the most common cause of failure of total joint arthroplasty, but a gold standard for PJI diagnosis is still lacking. Advanced glycation end products (AGEs) are proinflammatory molecules inducing intracellular oxidative stress (OS) after binding to their cell membrane receptors (RAGE). The aim of this study was to evaluate plasmatic soluble receptor for advanced glycation end products (sRAGE), as a new OS and infection marker correlating sRAGE to the level of OS and antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Accumulating evidence has suggested that sRAGE and AGEs seem to be contributing factors in the development of atherosclerosis, coronary artery disease [ 14 ], and peripheral artery diseases, irrespective of either renal impairment or diabetes mellitus (DM) [ 15 ]. Even though the elevated levels of sRAGE in diabetic patients have been linked to coronary artery disease [ 16 ], and AGEs have been designated to be a predictor for mortality because of cardiovascular diseases [ 17 , 18 ], recently sRAGE has been considered as an oxidative stress biomarker as well [ 19 ]. In addition, sRAGE is used as a biomarker for reflecting the RAGE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that sRAGE and AGEs seem to be contributing factors in the development of atherosclerosis, coronary artery disease [ 14 ], and peripheral artery diseases, irrespective of either renal impairment or diabetes mellitus (DM) [ 15 ]. Even though the elevated levels of sRAGE in diabetic patients have been linked to coronary artery disease [ 16 ], and AGEs have been designated to be a predictor for mortality because of cardiovascular diseases [ 17 , 18 ], recently sRAGE has been considered as an oxidative stress biomarker as well [ 19 ]. In addition, sRAGE is used as a biomarker for reflecting the RAGE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Being a soluble receptor, sRAGE binds AGEs but does not lead to any signaling pathway, thus competing with the signaling, cell-bound RAGE receptor and, as a consequence, limiting the AGEs-RAGE axis detrimental action and tissue damage [ 45 ]. For this reason, in many diseases, sRAGE is not only a marker of inflammation but also a protective factor [ 46 ]. Being present as a soluble form in circulation, sRAGE can be easily measured and has already been described as a biomarker in several diseases, ranging from cardiovascular to renal and liver disorders and sepsis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that serum levels of sRAGE are influenced by gender, age, ethnicity, the imbalance between antioxidants and prooxidants and inflammatory processes [27]. There are studies which attribute to sRAGE the role of a potential biomarker of oxidative stress [34]. Some reports have suggested that the overexpression of sRAGE reflects the excessive inflammatory response involved in the progression of endothelial lesions and coagulopathy associated with severe infection.…”
Section: Discussionmentioning
confidence: 99%